The Great British Music Hall: Its Importance to British Culture and ‘The Trivial’ - Steven Gerrard (Culture Unbound: Journal of Current Cultural Research, 2013)
By 1960, Britain’s once-thriving Music Hall industry was virtually dead. Theatres with their faded notions of Empire gave way to Cinema and the threat of Television. Where thousands once linked arms singing popular songs, watch acrobatics, see feats of strength, and listen to risqué jokes, now the echoes of those acts lay as whispers amongst the stalls’ threadbare seats.